Regional Budget Policy Related to Handling of Covid-19 In Kupang City - BENU, Esra D.N.A; SYAFRUDDIN, Akhmad; DARI, Alfridus SD. (PT Keberlanjutan Strategis Indonesia, 2021)
This study aims to have a deep, thorough, and detailed understanding of budget policies and provide a broad explanation of how to handle the budget during the COVID-19 pandemic in Kupang City. The data was collected through direct interviews with the local government which included the Head of the Regional Finance Agency, the Head of the Health Service, the Head of the Social Service, and the Head of the Budget Agency of the Kupang City Regional People's Representative Council (DPRD). All data obtained were analyzed through data reduction or summary, selecting and focusing on important information, and then discarding unimportant information; data is displayed in short descriptions, charts, relationships. The results show that the Kupang City Government first issued the Kupang Mayor Regulation No. 11 relating to the third amendment to the Kupang Mayor Regulation No. 45 of 2019 concerning the Elaboration of the Regional Revenue and Expenditure Budget with a total relocation budget of Rp. 21,950,052,750. This total budget is focused on personnel expenditure, goods and services, as well as capital expenditure for handling COVID-19. The government then issued the Kupang Mayor Regulation Number 13 of 2020 concerning the Fifth Amendment to the Kupang Mayor's Regulation Number 45 of 2019 concerning the Elaboration of the City Regional Revenue and Expenditure Budget with a Total Budget of Rp. 22,197,960,000. This total budget is intended for social safety nets with 22,054 recipients in the form of basic necessities worth Rp. 300,000.